Pretreatment of Lignocellulosic Biomass for the Growth of Oleaginous Microorganism as a Source of Biodiesel Production - Niti Srivastava; Kumar Gaurav (International Journal of Pharma and Bio Sciences, 2021)
The industrial production of sustainable and renewable alternative of existing fuels, biodiesel, is hampered by the increasing cost and exhausting emission of edible and non-edible oil such as sunflower oil, palm oil, jatropha oil, etc. However, the main disadvantage of using these oils as a feedstock is that they directly compete with human food, which results in shortage of oil supplies worldwide. To combat this problem, microbial oil, also known as single cell oil, has been suggested as an alternative feedstock for more sustainable biodiesel production. These microbial oils are produced from oleaginous microorganism i.e. microalgae, bacteria, fungi and yeast. Among all oleaginous microorganisms, oleaginous yeast have recently gained significant attention as they can accumulate higher quantities of microbial lipids mostly in the form of triacylglycerol and fatty acids having similar profiles as those of vegetable oil. The major advantages of oleaginous yeast are higher growth rate, shorter life cycle and easier scale-up, no effect on season and climatic condition. The low-cost substrates are potential feedstock for microbial lipid production. Lignocellulosic materials can be used as a sustainable substrate for the growth of oleaginous microorganisms, as they are abundant, low cost and renewable. The major constituents of lignocellulosic biomass are cellulose, hemicellulose and lignin, which are linked with each other and make it rigid and recalcitrant. Pretreatment methods help in order to degrade the crystallinity of cellulose fibres and to remove lignin from biomass. The present paper discussed the different pretreatment methods for lignocellulosic material viz., physical, chemical and biological, to make cellulose more accessible for hydrolytic enzymes.